(untitled) (Research, Society and Development, 2020)
Spirituality and religiosity have the potential to mobilize specific knowledge and influence the way individuals experience health and disease, adding to Nursing, new models of care and respecting current health policies. The purpose of this article is to reflect on the dimensions of spirituality and religiosity in comprehensive care with a view to apprehending comprehensive health and nursing care. This is a reflective article, for which a search was made for productions dealing with the topic in the Virtual Health Library (VHL) and Pubmed. Thus, it was organized into two thematic blocks: spirituality, religiosity and nursing care; and comprehensive care as a basis for comprehensive health and nursing care in the context of the dimensions of spirituality and religiosity. It is observed that the approach to spirituality and religiosity (E/R) finds fertile ground in the field of health, where it aims to consummate comprehensiveness as a guiding principle of SUS and, simultaneously, the promotion of comprehensive care. Likewise, the integrality of health care is comprehensive, deep and complex, in defining the way the patient or user of the health system should be treated, that is, as a whole. These are not recente and antagonistic issues for health área, ando it is therefore importante to invest effors in the production of new studies and so that they can effectively integrate thes training and daily professionals practise.